The Role of Abdul Muis in the Youth Movement in Bandung 1913-1935 - Via Nurhasanah; Achmad Achmad (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The purpose of this study is to analyze the activities and contributions of Abdul Muis in strengthening the Sarekat Islam, to describe the political landscape of Bandung during that period, and to explore its impact on the development of the organization as well as the local community. This research employs the historical method with a qualitative approach. Data were collected through the stages of heuristics (source collection), criticism (source evaluation), interpretation (data analysis), and historiography (historical writing). The findings show that Abdul Muis played a central role in advancing Sarekat Islam in Bandung through his charismatic and strategic leadership. He succeeded in strengthening the organization by building networks, mobilizing the masses, and voicing resistance against Dutch colonial rule. Moreover, Abdul Muis’s contributions had a significant influence on raising nationalist awareness among the local community and shaping the political dynamics of Bandung during that period. This study is expected to enrich the understanding of the early history of Indonesia’s national movement and the role of key figures such as Abdul Muis in shaping socio-political dynamics.